Primary Basic Subject by Distillation - Neelameghan, A. (Journal of Information and Knowledge, 1973)
The formation of Primary Basic Subjects by the Distillation mode is discussed. The arrangement of the Distilled Primary Basic Subjects in a helpful sequence in the schedule of Basic Subjects in the Colon Classification is explained.